Deep Hypothermic Cardiac Arrest Treated by Extracorporeal Life Support in a Porcine Model: Does the Rewarming Method Matter?. (13th February 2016) - Debaty, Guillaume; Maignan, Maxime; Perrin, Bertrand; Brouta, Angélique; Guergour, Dorra; Trocme, Candice; Bach, Vincent; Tanguy, Stéphane; Briot, Raphaël
Abstract: Objectives: Extracorporeal life support (ECLS) is the reference rewarming technique of accidental deep hypothermic cardiac arrest (DHCA). This study was designed to examine the impact of different rewarming blood flow rates and temperature setting of ECLS on cardiopulmonary lesions after DHCA in a porcine model of accidental hypothermia. Methods: Twenty‐four pigs were cannulated for ECLS, cooled until DHCA occurred, and subjected to 30 minutes of cardiac arrest. During the rewarming phase, we compared a low blood flow rate of 1.5 L/min versus a high flow rate of 3.0 L/min as well as two‐temperature‐setting rewarming strategies: a temperature during ECLS adjusted to 5°C above the central core temperature versus 38°C maintained throughout the rewarming phase. Cardiac output, hemodynamics and pulmonary function parameters were evaluated. Biologic markers of ischemia‐reperfusion injuries were analyzed at baseline and at the end of the experiment. Results: DHCA occurred at 21.2 ± 2°C. There was a trend for better cardiac output in groups with high blood flow (p = 0.053), with no interaction between ECLS flow and temperature (p = 0.63), a trend toward lower pulmonary vascular resistance (PVR; p = 0.075) and a significant decrease in arterial PVR in groups with high blood flow (p = 0.013) with no interaction (p = 0.47 and p = 0.60 for PVR and arterial PVR, respectively). Serum interleukin‐6, tumor necrosis factor‐α, receptor for advanced glycation end products (RAGE), and neuron‐specific enolase were significantly increased between baseline and endpoint. The increase in the serum RAGE concentration was higher in the 38°C rewarming temperature groups compared to 5°C above adjusted temperature. There were no other significant differences in biomarkers. Conclusions: We developed a porcine model of DHCA treated by ECLS. Our data suggest that cardiac output tended to improve with a high‐flow‐rate rewarming strategy while a high‐temperature delta between core temperature and ECLS increased the RAGE markers of lung injury.